REKAMAN CLOSED CIRCUIT TELEVISION (CCTV) SEBAGAI ALAT BUKTI DALAM TINDAK PIDANA KORUPSI SETELAH KELUARNYA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 20/PUU-XIV/2016 - Renhard Pebrian; Erdianto Effendi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The number of defendants in corruption cases that were decided freely by the general court or district court was based on various reasons, one of which was that the criminal act of corruption charged with the defendant was not proven. Admittedly, corruption is an offense whose proof can be said to be very difficult. Many aspects must be fulfilled in order to truly prove that a defendant has committed a criminal act of corruption. Proof of corruption is considered more difficult than other criminal acts. For that we need an extraordinary effort also in proving it. One of them can use evidence in the form of Closed Circuit Television (CCTV).This type of legal research is normative legal research that focuses on synchronizing law. Meanwhile, if seen from the nature of this research is descriptive. This study uses secondary data that is ready-made data. Activities undertaken in collecting data in this study are the study of documents or library materials.The results of this study are The use of CCTV in cases of criminal acts of corruption according to several court decisions prior to the Constitutional Court decision Number 20 / PUU-XIV / 2016 that in the Criminal Procedure Code in Article 184 only states that valid evidence is witness testimony, expert testimony, letters, instructions and statements of the defendant. . Apart from the evidence tools mentioned above, according to the Criminal Procedure Code it is not justified to be used as evidence to prove the guilt of the accused. However, in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, the use of CCTV footage can be used as valid evidence. Likewise in the Law of the Republic of Indonesia Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crime that legal evidence for criminal acts of corruption can also be obtained from other evidence in the form of pronounced information, sent, received or stored electronically by an optical device or similar device. This interpretation also applies even though there are no electronic information phrases or words and / or electronic documents found. The use of CCTV in cases of criminal acts of corruption according to several court decisions after the Constitutional Court decision Number 20 / PUU-XIV / 2016, namely the provision of a lex specialist regarding the use of digital evidence in the form of the use of CCTV, which can be used as valid evidence in the proving process. a criminal act of corruption, which is an extension of evidence by fulfilling the following matters, namely: 1) The act of recording with CCTV must be known and approved by the person to be recorded, by notifying that the place or room has been installed or equipped with a CCTV camera . 2) The CCTV footage to be used as evidence must be in its original form, not edited.Keywords: CCTV recordings, evidence, corruption